A polyphasic approach to the study of the genus Nitzschia (Bacillariophyta): three new planktonic species from the Adriatic Sea. Issue 1 (15th December 2020) - Mucko, Maja; Bosak, Sunčica; Mann, David G.; Trobajo, Rosa; Wetzel, Carlos E.; Peharec Štefanić, Petra; Ljubešić, Zrinka
Abstract : The paraphyletic diatom genus Nitzschia comprises over 1000 morphologically distinct pennate taxa, known from the benthos and plankton of freshwater, brackish, and marine environments. The principal diagnostic characters for delimitation of Nitzschia species include valve shape, the position and structure of the raphe, presence/absence and shape of the proximal raphe endings and terminal raphe fissures, areola structure, and specific morphometric features such as cell size, and stria and fibula density. In this study, we isolated 12 diatom strains into culture from samples collected at the surface or greater depths of the southeastern Adriatic Sea. Morphological analyses included LM, SEM, and TEM observations, which, along with specific morphometric features, allowed us to distinguish three new Nitzschia species. These findings were congruent with the results of phylogenetic analyses performed on nuclear‐encoded SSU (18S) rDNA and chloroplast‐encoded rbc L and psb C genes. One of the new species ( Nitzschia dalmatica sp. nov.) formed a lineage within a clade of Bacillariaceae containing members of the Nitzschia sect. Dubiae, which was sister to Psammodictyon . A second lineage was part of a novel clade that is significantly distinct from other Nitzschia species sequenced so far and includes Nitzschia adhaerens sp. nov. and N. cf. adhaerens . A further new species was found, Nitzschia inordinata sp. nov., which appeared as the sister group to the N. adhaerens clade and the conopeoid Nitzschia species in our phylogenetic trees. Our findings contribute to the overall diversity of genus Nitzschia, especially in identifying some deep branches within the Bacillariaceae, and highlight under‐scoring of this genus in marine plankton.